Self-care health behaviors in nursing students during COVID-19 - Salas Osorio, Yenina Angelica (2021)
Objective. To identify self-care behaviors in the physical and mental health of female students enteringthe Academic Nursing Program duringthe COVID-19 pandemic in the 2021-1 semester at Universidad de Huánuco. Methods. It was a quantitative, descriptive and cross-sectional study. The sample population consisted of 126 students entering the Academic Nursing Program. A scale of self-care behaviors was applied. Measurements of frequency and proportions were used. Results. 60.9 % (77) of students demonstrated healthy self-care behaviors in the physical health dimension, compared to 51.7% (65) with unhealthy self-care behaviors in the mental health dimension. In general, there was a predominance of healthy self-care behaviors [55,8 % (70)]. When comparing the sociodemographic characteristics of the sample under study, according to the types of self-care (healthy/unhealthy), it was found that, both among women and in the group of adolescents, students who only study and those who live with their parents show more healthy self-care. Conclusions. There is a predominance of healthy self-care behaviors in the dimensions: mental and physical self-care.